2016
DOI: 10.1248/bpb.b16-00017
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Inhibits the Proliferation of C6 Glioma Cells <i>via</i> the Translocation of Unphosphorylated Glucocorticoid Receptor

Abstract: Astroglial cells have been considered to have passive brain function by helping to maintain neurons.However, recent studies have revealed that the dysfunction of such passive functions may be associated with various neuropathological diseases, such as schizophrenia, Alzheimer's disease, amyotrophic lateral sclerosis and major depression. Corticosterone (CORT), which is often referred to as the stress hormone, is a well-known regulator of peripheral immune responses and also shows anti-inflammatory properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A recent study indicated that treatment with cortisone for 24 h resulted in a decrease in the proliferation of C6 cells in a dose-dependent manner due to the translocation of GR in the nucleus. These effects were GR dependent since the addition of mifepristone, a GR antagonist blocked the effect of cortisone [95]. No clinical studies addressed the specific role of either GRα or GRβ isoforms or mineralocorticoid receptors that are both expressed in glioma cells, although this could help to understand the precise mechanism of action of dexamethasone or other corticoids.…”
Section: Exogenous Glucocorticoids Exposure: Still Incomplete and Debmentioning
confidence: 99%
“…A recent study indicated that treatment with cortisone for 24 h resulted in a decrease in the proliferation of C6 cells in a dose-dependent manner due to the translocation of GR in the nucleus. These effects were GR dependent since the addition of mifepristone, a GR antagonist blocked the effect of cortisone [95]. No clinical studies addressed the specific role of either GRα or GRβ isoforms or mineralocorticoid receptors that are both expressed in glioma cells, although this could help to understand the precise mechanism of action of dexamethasone or other corticoids.…”
Section: Exogenous Glucocorticoids Exposure: Still Incomplete and Debmentioning
confidence: 99%
“…Nakatani et al (24), showed that corticosterone inhibited the proliferation of C6 glioma cells. However, in our present study, corticosterone did not inhibit the cell viability in U-87 MG cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific mechanism by which NFκB blocks p53 activity during low‐grade inflammation is not well documented. Several important molecules have been targeted in order to inhibit the proliferative transitions in cancer cells, one such molecule being corticosterone, a stress hormone that acts through the glucocorticoid receptor pathway and is a well‐known regulator of peripheral immune responses showing anti‐inflammatory/proliferative properties . Furthermore, it is known that overexpression of glucocorticoid‐induced tumor necrosis factor (TNF) receptor function retards proliferation in multiple myeloma cells through the modulation of NFκB and p53 proteins …”
Section: Introductionmentioning
confidence: 99%
“…Several important molecules have been targeted in order to inhibit the proliferative transitions in cancer cells, one such molecule being corticosterone, a stress hormone that acts through the glucocorticoid receptor pathway and is a well-known regulator of peripheral immune responses showing antiinflammatory/proliferative properties. 17 Furthermore, it is known that overexpression of glucocorticoid-induced tumor necrosis factor (TNF) receptor function retards proliferation in multiple myeloma cells through the modulation of NFjB and p53 proteins. 18 It has been reported previously that, fluoxetine, a selective serotonin reuptake inhibitor, is able to act as an anticancer agent by virtue of its ability to reduce acute murine colitis through inhibition of the NFjB pathway.…”
Section: Introductionmentioning
confidence: 99%